DAKWAH MEDIA SOSIAL : POLA DAKWAH PADA MASA PANDEMI COVID 19 - Zida Zakiyatul Husna; Moh. Ali Aziz (Mediakita, 2021)
The Covid-19 pandemic, which has hit almost all parts of the world, has made many changes in social order. No exception, Indonesia is also one of the countries affected by the Covid-19 outbreak. The new government policy regarding the prevention of the Covid-19 outbreak has hampered almost all social activities. One of them is da'wah activities. The existence of the PSBB and WFH policies makes preachers have to find new da'wah strategies and methods so that da'wah can be carried out in the midst of new policies from the government. Looking at the above background, this research focuses on how the new dakwah patterns during the pandemic. Through a descriptive qualitative approach and observing one of the da'wah actors, namely the @ala_nu account on social media Instagram, this study found that one of the new da'wah patterns in the pandemic was the use of growing media. And one of the media that is now widely used by preachers in conveying their preaching during a pandemic is Instagram social media. Through the @ala_nu account, researchers can find out new da'wah patterns using social media.